Concepções de professores/as de ciências sobre sexualidade em alunos/as com deficiência intelectual - Cruz, Tatiana Pinheiro (2023)
Sexuality is part of human life and is linked to the development of each individual with or without disabilities. Sexuality is influenced by several aspects, including biological, psychosocial and social aspects. Thus, the present investigation has a qualitative approach with a case study bias, seeking to understand the conception of Science teachers in the 8th year of Elementary School about the sexuality of students with Intellectual Disabilities (ID) in the municipality of Itabaiana in Sergipe state. Thus, in an attempt to organize the information from the theoretical framework, structuring axes are proposed based on the perspective that each author defends. In the first axis, we have Maia and Ribeiro (2011), who discuss the myths and prejudices about the sexuality of intellectually disabled people. In the second axis, we have Figueiró (2018), who highlights the relevance of the role of the teacher and the student in the active process on Sexual Education (SE). In the third axis, Foucault (1997) stands out, who discusses the history of sexuality in the West, and Furlani (2008), who makes notes on SE approaches in contemporary times. The technique for obtaining data was a semi-structured interview, following a script of open and closed questions, with the aim of collecting information that is of interest to the investigation (Gil, 2008). Once we had the data, each report was transcribed and analyzed from the perspective of Bardin (2016). It was possible to identify, in the results, that the majority of Science teachers have a comprehensive conception of sexuality, represented by aspects involving the biological, psychological and social dimensions of human sexuality. Although sexuality is part of the life of any human being, with or without disabilities, this topic is still full of taboos. However, when referring to the sexuality of people with Intellectual Disabilities, it has still been the target of prejudices, myths and even lack of knowledge, often being labeled as naive and instinctive. Overall, it is as if person with disability do not have the right to fully live their sexuality and their affections, specifically related to beliefs and “myths”.